Covert Insubordination in Arus Balik Novel of Pramoedya Ananta Toer: Perspective of Social Movements - Sudikan, Setya Yuwana; Tjahjono, Tengsoe (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The aim of this study was to describe the covert insubordination in Arus balik Novel of Pramoedya Ananta Toer. The theory used is a covert insubordination theory within perspective of social movements. This theory was the rational actions of individual leaders but not in the category of rational choice theory, there are not open, take place informally, not stated, and on a small scale. This study applied a descriptive qualitative approach. Data source Arus balik Novel of Pramoedya Ananta Toer. The data of this research were word, phrase, sentence, paragraph, and discourse associated with the focus of the research.The technique of data analysis techniques was hermeneutics. Research procedures, namely: 1) heuristics, and 2) retroactive. The findings of this study suggests there are five figures shrouded in insubordination, namely: 1) covert insubordination Arya Teja Wilwatikta against Majapahit, 2) covert insubordination against AdipatiÂ  Cluring Rama Arya Teja Wilwatikta, 3) betrayal of Adipati Wilwatikta against the Adipati Unus who deliberately late five days of sending the troops to attack Portuguese in Malacca Strait result in Jepara's forces easily defeated by Portuguese, 4) betrayal of Sunan Rajeg (Isaac Indrajit) against the Adipati Wilwatikta patterned economic resentment and because it removed from Office as Harbour replaced Sayid Habibullah Almasawa, 5) betrayal of Sayid HarbourÂ  Habibullah Almasawa which has a political agenda like to master and monopolize trade in Tuban port who conspired with Portuguese trading fleet in Tuban area, and 6) covert insubordination against Chief Minister Wiranggaleng Tuban and Adipati Arya Teja Wilwatikta.Â